(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Hospitality is a diverse field, a different market market, a part of economic and social life that provides many possibilities for growth of small enterprises, but often extremely efficient resources. In this sense, its association with entrepreneurship takes note of the goals of building new competitive enterprises by strengthening the potential and ability of organisations in establishing, planning, handling risk and benefit. By identifying micro factors impacting the advancement of local business and the hospitality sector, the paper aimed at examining entrepreneurs’ actions in compliance with market restrictions, restricting creativity, growth and behaviour. Enterprise would improve competition in the hospitality sector, contributing to improved efficiency and economic growth.